Role of indoleacetic acid-lysine synthetase in regulation of indoleacetic acid pool size and virulence of Pseudomonas syringae subsp. savastanoi. - Glass, N L (1988)
The phytopathogen Pseudomonas syringae subsp. savastanoi incites the production of galls on olive and oleander plants. Gall formation is dependent upon the bacterial synthesis of the phytohormone indole-3-acetic acid (IAA). Strains isolated from oleander galls are capable of further metabolizing IAA to an amino acid conjugate, 3-indoleacetyl-epsilon-L-lysine (IAA-lysine); bacterial olive gall isolates lack this activity. In this study, the cloned gene for IAA-lysine synthetase (iaaL+) was introduced into strains isolated from olive and oleander galls to determine its effect on the regulation of IAA pool size and virulence. IAA-lysine was synthesized by isolates from olive galls when iaaL+ was introduced by conjugation, but the amount of IAA which accumulated in culture by the transconjugant was reduced by one-third. When the iaaL+ locus of an oleander gall isolate was inactivated by Tn5 mutagenesis, the resulting mutant did not convert IAA to IAA-lysine; however, it accumulated fivefold more IAA in culture than the wild type did. When inoculated into oleander plants, the iaaL mutant did not cause typical gall symptoms, nor did it replicate within host tissue similarly to the wild type.